Medical surveillance of the work of the clinic-based midwife - J. V. Larsen (AOSIS, 1979)
The comprehensive Health Programme of the South African Department of Health is based upon the concept of a base hospital linked with peripheral clinics staffed by nursing sisters. Supervision and training of such nurses is normally carried out by medical staff visiting from the base hospital. In the case of midwifery, the methods of medical supervision of the staff must be different from those employed in a hospital situation.